5 questions on Agile - Ruma, Laurel (O'Reilly, 2018)
"In this interview, O'Reilly Media Content Director Laurel Ruma talks to Dom Price, head of R & D and work futurist at Atlassian, about how Atlassian applies Agile practices."--Resource description page